Impact of Foreign Investment and Natural Resources Sharing Funds Against Environmental Degradation in Indonesia - ., Priyagus (KnE Social Sciences, 2018)
This study examines the impact of foreign investment as a reflection of economic globalization and fiscal policy in the form of natural resource revenue sharing in development against environmental degradation, especially water in Indonesia. Using 33 provincial panel data during 2011-2015 with the basic model of EKC’s of cubic forms. The results explain that is a relationship between income and degradation that support the EKC hypothesis, but it not significantly. Foreign investment has a positive and significant impact on increasing degradation, while fiscal policy has a negative and not insignificant impact on reducing environmental degradation. Natural Resources Sharing Funds are not entirely used for environmental costs but are also used to provide basic infrastructure. The government needs to increase supervision of foreign capital, increase revenue sharing for natural resources and focus more on improving the environment. Keywords: EKC, Foreign Invesmen, Sharing Funds Natural Resource, Water Degaradation.